PERLINDUNGAN HUKUM TERHADAP HAK CIPTA MOTIF BATIK KUNINGAN BERDASARKAN UNDANG-UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA (Studi Kasus di Kabupaten Kuningan) - Siti Latifah; Anthon Fathanudien (Mahkamah : Jurnal Kajian Hukum Islam, 2020)
This research is motivated by the Copyright Law No. 28 of 2014 that Indonesia is an archipelagic country which has a very rich diversity of arts and culture. This is caused by the diversity of ethnic groups, ethnicities, languages, traditions and religions that as a whole are the potential of a protected nation. This research is an empirical juridical type of research that is analytical descriptive with a qualitative approach. The types of data used are primary data, secondary data and tertiary data. Data collection techniques by interviewing, observing and studying literature. This research was conducted in the Cikubangsari Village, Kuningan Regency. The results of this study are the enactment of Law Number 28 of 2014 concerning Copyright related to legal protection and registration of Copyright listed in Article 66 paragraph (1) of Law Number 28 of 2014 concerning Copyright. As for the implementation of Law No. 28 of 2014 concerning Copyright namely from the many Kuningan batik motifs in Kuningan it turns out that not all of the Kuningan batik motifs are registered and only 10 motifs from 20 motifs registered with a total of 120 Kuningan batik motifs owned by batik artisans Kuningan, which is located in the Cikubangsari Village, Kuningan Regency, while the batik business owner in Kuningan has not registered the Kuningan batik motif copyright